Whole Systems Thinking and Context of the University Teacher on Curricular Sustainability in Primary Education Teaching Degrees at the University of Zaragoza - Silvia Lorente-Echeverría; Inma Canales-Lacruz; Berta Murillo-Pardo (MDPI AG, 2023)
The traditional, mechanistic university context is far from achieving commitment and accountability for Education for Sustainable Development (ESD). The whole structure must be redefined in terms of teaching, research, management, and the connection with the whole community. The main objective is based on identifying the cognitive perception that university teachers have in relation to curricular sustainability, and how this is linked to the context in which they develop their teaching practice. The sample is made up of 15 teachers, selected purposively and non-randomly: 3 women and 12 men, with a mean age of 45.57 ± 9.72. The information was obtained from focus groups, using a semi-structured questionnaire. The QRS NVIVO 12 software program was used for content analysis. The results show a preponderant lack of knowledge, skills, and abilities in sustainability, given a lack of attitude towards change. The results show that the transformation lies in teacher training, based on workshops, courses, or experiential activities. Finally, assessing their own context, the participants highlighted the lack of a joint institutional strategy on sustainability.